Shifting Feeding Habits During Settlement Among Small Yellow Croakers (Larimichthys polyactis) - Chen, Yuange; Wang, Weilong; Zhou, Wei; Hu, Fen; Wu, Meiqin (Frontiers in Marine Science, 2022)
The small yellow croaker, Larimichithys polyactis, is a keystone species in the Yellow Sea and the East China Sea and significantly impacts local ecosystems, has been through decades of resource decline. Settlement of post-larvae is another period with high mortality other than first feeding, thus affect the recruitment and survival. We examined the feeding habits of 49 post-larvae and early juveniles of L. polyactis in the Yangtze River estuary, an important nursery of many fishes. In order to obtain more detailed feeding habits, we introduced the method of DNA barcode to examine the gastrointestinal contents. Two groups are carried out by TA cloning and Miseq high-throughput sequencing, respectively. The results of both groups revealed that the dietary breadth enlarged with body length increase. The dominance of copepods in diet decreased with body length increasing. Post-larvae (<17 mm in body length in this study) mainly feed on copepods. At the beginning of settlement (17 mm – 19 mm in body length), L. polyactis ingested larger organisms like fishes and mysids, along with copepods. Larger early juveniles (>20 mm in body length) have a much wider dietary breadth, implying successful settlement. The species numbers in the Miseq group are significantly larger than in the TA clone group, making the trend more pronounced within the Miseq group. We recommend investigating feeding habits of larval by combing Miseq and visual examination in the future.